Introducing cyclic alkyl chains into small-molecule acceptors for efficient polymer solar cells. Issue 26 (22nd June 2018) - Li, Renlong; Liu, Gongchu; Xie, Ruihao; Wang, Zhenfeng; Yang, Xiye; An, Kang; Zhong, Wenkai; Jiang, Xiao-Fang; Ying, Lei; Huang, Fei; Cao, Yong
Abstract : A new acceptor–donor–acceptor type small molecule acceptor, namely IDT-HN, is developed, which consists of a newly developed 2-(3-oxo-2, 3, 5, 6, 7, 8-hexahydro-1 H -cyclopenta[ b ]naphthalen-1-ylidene)malononitrile as the peripheral electron-withdrawing group. Abstract : A new acceptor–donor–acceptor type small molecule acceptor, namely IDT-HN, has been developed, which consists of a newly developed 2-(3-oxo-2, 3, 5, 6, 7, 8-hexahydro-1 H -cyclopenta[ b ]naphthalen-1-ylidene)malononitrile as the peripheral electron-withdrawing group and indaceno[1, 2- b :5, 6- b ′]dithiophene as the electron-donating core. Compared with the reference molecule (IDT-IC) that bears phenyl-fused indanone as the end groups, IDT-HN exhibited an elevated lowest unoccupied molecular orbital level. By utilizing IDT-HN as the electron acceptor and a wide bandgap conjugated polymer, PBDB-T, as the electron donor, optimized devices exhibited an impressively high power conversion efficiency of up to 10.22% with simultaneously improved open-circuit voltage, short-circuit current and fill factor. The improved photovoltaic performance can be attributed to the widened and intensified absorption spectra, improved electron mobility, more ordered π–π packing structure, and the symmetric carrier transport mobility of the IDT-HN-based blend in comparison to those obtained from devices based on the reference molecule IDT-IC. These results indicate that the cyclic alkyl moiety incorporated into the peripheral groups plays a critical role in improving the performance of the corresponding solar cell devices. In addition, the power conversion efficiency of the devices remains at 91% of its optimum performance with a film thickness of 250 nm, indicating its great potential for future practical application.